Germline masculinization by Phf7 in D. melanogaster requires its evolutionarily novel C-terminus and the HP1-family protein HP1D3csd - Shu Yuan Yang (Nature Portfolio, 2021)
Abstract Germ cells in Drosophila melanogaster need intrinsic factors along with somatic signals to activate proper sexual programs. A key factor for male germline sex determination is PHD finger protein 7 (Phf7), a histone reader expressed in the male germline that can trigger sex reversal in female germ cells and is also important for efficient spermatogenesis. Here we find that the evolutionarily novel C-terminus in Phf7 is necessary to turn on the complete male program in the early germline of D. melanogaster, suggesting that this domain may have been uniquely acquired to regulate sexual differentiation. We further looked for genes regulated by Phf7 related to sex determination in the embryonic germline by transcriptome profiling of FACS-purified embryonic gonads. One of the genes positively-regulated by Phf7 in the embryonic germline was an HP1family member, Heterochromatin Protein 1D3 chromoshadow domain (HP1D3csd). We find that this gene is needed for Phf7 to induce male-like development in the female germline, indicating that HP1D3csd is an important factor acting downstream of Phf7 to regulate germline masculinization.